Why, how-to, and cost of programed AI breeding of dairy cows - Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1998)
Management of the estrous cycle is now more practical than it was a decade ago because of our understanding of follicular waves. With availability of three gonadotropin-releasing hormone (GnRH) products and two prostaglandin products, the cycle can be controlled for fixed-time inseminations with little loss in conception rate compared to inseminations after detected estrus. Various systems are effective for programming first inseminations with or without some heat detection. With the incorporation of transrectal ultrasonography for early pregnancy diagnosis 28 to 30 days after insemination, routine heat detection programs could be eliminated by reprogramming each cow after an open diagnosis. The most limiting factor in the control of the cycle is the proportion of missed heats in estrus-synchronization programs that rely partly or solely on heat detection. Pregnancy rate (the proportion of cows that become pregnant of all cows programmed for insemination) is the best measure of an estrussynchronization program, because it measures total number of pregnancies achieved per unit of time rather than simple conception success at any given insemination.; Dairy Day, 1998, Kansas State University, Manhattan, KS, 1998;
Keywords: Dairy Day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-158-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 821; AI breeding; GnRH; Prostaglandin F2; Programmed breeding; Economics